Invitational Counselling: An Expanded Framework for Comprehensive School Counselling Programs - Schmidt, John J. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article presents an overview of invitational counselling, an approach to counselling based on self-concept theory, perceptual psychology, and invitational theory. The approach is encouragedas an expanded framework for designing comprehensive school counselling programs of services for students, parents, and teachers.